Prevalence of Neuropathic Pain in Rheumatic Disorders: Association With Disease Activity, Functional Status and Quality of Life - Yesim GARİP,; Filiz ESER,; Ayşegül KILIÇARSLAN,; Hatice BODUR, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate neuropathic pain in rheumatologic disorders including rheumatoid arthritis (RA), ankylosing spondylitis (AS), and osteoarthritis (OA) using PainDETECT and to determine its effect on the quality of life in terms of disease activity, functional status, social and emotional functioning. Patients and methods: A total of 150 patients (66 males, 84 females; mean age 48.44±12.22 years; range 25 to 65 years) were included in the study. Of these patients, 50 had OA, 50 had RA, and 50 had AS. Control group consisted of 50 healthy subjects (20 males, 30 females; mean age 48.36±12.68 years; range 25 to 65 years). OA severity was evaluated by Western Ontario and McMasters Universities Index of Osteoarthritis. In RA patients, Disease Activity Score-28 was used for measuring disease activity, and Stanford Health Assessment Questionnaire for functional status. In AS patients, disease activity was assessed by Bath Ankylosing Spondylitis Disease Activity Index and functional status by Bath Ankylosing Spondylitis Functional Index. Neuropathic pain was determined by PainDETECT questionnaire and quality of life by Nottingham Health Profile. Results: Prevalence of neuropathic pain was 44% in OA, 28% in AS, and 18% in RA patients. Compared with control patients, prevalence was higher in OA [Odds ratio=12.46 95% confidence interval (3.89-39.85)] (p=0.00) and AS patients [Odds ratio=4.47 95% confidence interval (1.36-14.76)] (p=0.009). In OA patients, PainDETECT was correlated with Western Ontario and McMasters Universities Index of Osteoarthritis (p=0.00). In all of the patient groups, PainDETECT was correlated with Nottingham Health Profile (p=0.00). Physical mobility subgroup showed the strongest correlation with PainDETECT. Conclusion: Our study demonstrated that neuropathic pain is strongly associated with quality of life in terms of physical mobility, energy, sleep, and social and emotional functions. The disease with highest prevalence of neuropathic pain was OA. A better understanding of neuropathic pain mechanisms in rheumatic diseases will help us find more effective treatment strategies.